2014
DOI: 10.1007/s00415-014-7589-z
|View full text |Cite
|
Sign up to set email alerts
|

Taste function in early stage treated and untreated Parkinson’s disease

Abstract: Since brain stem regions associated with early Parkinson's disease (PD) pathology encroach upon those involved in taste function, the ability to taste may be compromised in PD. However, studies on this point have been contradictory. We administered well-validated whole-mouth and regional taste tests that incorporated multiple concentrations of sucrose, citric acid, caffeine, and sodium chloride to 29 early stage PD patients and 29 age-, sex-, and race-matched controls. Electrogustometry was also performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
3
29
1
Order By: Relevance
“…Most of the studies on this topic published afterwards identified a reduced taste sensitivity in PD (ageusia) with an estimated frequency of taste impairment between 9 and 54% (Tarakad and Jankovic, 2017;Cossu et al, 2018;Doty and Hawkes, 2019). Only two groups showed higher sensitivity to taste stimuli in PD compared to controls (Sienkiewicz-Jarosz et al, 2013;Doty et al, 2015).…”
Section: Taste and Pdmentioning
confidence: 99%
“…Most of the studies on this topic published afterwards identified a reduced taste sensitivity in PD (ageusia) with an estimated frequency of taste impairment between 9 and 54% (Tarakad and Jankovic, 2017;Cossu et al, 2018;Doty and Hawkes, 2019). Only two groups showed higher sensitivity to taste stimuli in PD compared to controls (Sienkiewicz-Jarosz et al, 2013;Doty et al, 2015).…”
Section: Taste and Pdmentioning
confidence: 99%
“…Doty et. al., [16] employed procedures like ours, and found no gender differences in their 1 0 whole mouth taste test. Our study showed no gender differences in the same age group.…”
Section: Discussionmentioning
confidence: 59%
“…It was disrupted in patients with PD. It has been well-documented that vision, smell, hearing, and taste sensations are impaired in patients with PD [43][44][45][46][47]. Dopamine deficiency may have been a factor at the periphery, but not necessarily at the central Parkinson's disease has recently become noticeable with nonmotor symptoms, not motor findings.…”
Section: Discussionmentioning
confidence: 99%